(untitled) (Journal of Medical & Health Sciences Review, 2025)
Waterborne diseases continue to pose a significant health threat in developing countries, particularly in rural areas with limited access to clean water, proper sanitation, and adequate water treatment. This study investigated the prevalence of waterborne diseases in relation to water sources, treatment methods, and sanitation conditions across three tehsils of District Karak, Pakistan. A descriptive cross-sectional survey was conducted, analyzing 582 reported cases from Karak, Takht-e-Nasrati, and Banda Daud Shah tehsils. The overall distribution of waterborne diseases indicated that diarrhea was the most prevalent, accounting for 14.3% (83/582) of cases, followed by cholera at 10.0% (58/582), and typhoid at 7.6% (44/582). Hepatitis A, H. pylori, and constipation represented smaller proportions of the total reported cases, specifically 2.6% (15/582), 1.0% (6/582), and 0.3% (2/582), respectively. Tehsil-wise data showed that Karak (n=180) reported diarrhea as the most frequent disease at 16.7% (30/180), followed by typhoid at 12.2% (22/180). In Takht-e-Nasrati (n=202), diarrhea was also the most prevalent at 9.9% (20/202), with cholera following at 6.9% (14/202). Banda Daud Shah (n=200) exhibited the highest disease burden, with diarrhea at 16.5% (33/200), cholera at 15.0% (30/200), typhoid at 8.0% (16/200), and hepatitis A at 4.0% (8/200). Notably, cases of H. pylori and constipation were exclusively observed in Banda Daud Shah. Regarding water sources, wells were the primary source, used in 66.7% (388/582) of cases. Other sources included water tanks (13.4%, 78/582), tube wells (12.7%, 74/582), pressure pumps (9.4%, 55/582), bottled water (2.7%, 16/582), river streams (2.4%, 14/582), and natural sources (0.3%, 2/582). Water treatment practices were poorly adopted: only 9.1% (53/582) of respondents reported boiling water, 7.9% (46/582) used filtration, and just 1.4% (8/582) applied chemical treatment. Sanitation data revealed that flush toilets were widely used (93.1%, 542/582), while pit latrines (4.3%, 25/582) and open defecation (1.4%, 8/582) were still present in some households. In conclusion, diarrhea, cholera, and typhoid remain the most prevalent waterborne diseases in District Karak, with the greatest burden observed in Banda Daud Shah. Despite the high availability of flush toilets, the consumption of contaminated water continues to pose a serious public health risk.